Manipulative and inherent errors in anti-D quantitation using the AutoAnalyzer. Issue 3 (March 1972) - Gunson, H. H.; Phillips, P. K.; Stratton, F.
Abstract : The limits of accuracy for the quantitation of anti-D using the AutoAnalyzer have been reduced from ± 26% with manually prepared dilutions to ± 14% using an automatic pipette, as expressed by the 95% confidence limits. The error inherent in the AutoAnalyzer was estimated to contribute ± 10% to the overall error. Problems associated with the reproducibility of this method for anti-D quantitation have been investigated, namely, the effect of the age of a given test cell, the use of different test cells, loss of sensitivity of the machine over a given day, and the reproducibility of results obtained at different positions on the standard graph.